Detecção de patógenos de Apis mellifera L. (Hymenoptera, Apidae) em mel com PCR multiplex e seu uso em amostras brasileiras - Puker, A.; Teixeira, É. W.; de Paula, S. O.; Pinto, F. A.; Silva, I. C.; Santana, W. C.; Message, D. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Several pathogens attack the bees Apis mellifera L. (Hymenoptera: Apidae) around the world, such as the bacteria Paenibacillus larvae and the fungi Ascosphaera apis, Nosema apis and Nosema ceranae. Their distributions in some parts of the world, such as Brazil, are not fully known not only because c rmv s p . g o v . b r mv&z 55 I I e n d e s a of the difficulty of collecting samples such as in our large country, but also because of the time and the cost of diagnosis techniques involved. The analyze of the presence of the spores of honeybee pathogens in honey has shown to be a good strategy for epidemiological studies and early detection before the expression of symptoms in the colony. Therefore it is important the standardizantion of techniques for rapid diagnosis to facilitate the safe performance of the epidemiological surveys, and controlling the spread of these microorganisms. Here, we it was standardized a multiplex PCR technique for simultaneous detection of four pathogens of A. mellifera: A. apis, N. apis, N. ceranae and P. larvae in honey. This technique was used in honey samples from some Brazilian states. Sterile honey samples (20 mL) were artificially contaminated with all selected pathogens. These positive samples were diluted in 30 mL sterile water followed by centrifugation. DNA from pellet was extracted using a commercial kit. A Multiplex PCR was standardized using specific primers and a common melting temperature. Recommendations of national legislation were used for preparation of honey solutions submitted to the developed technique. Also it were prepared samples of honey collected from brood area, extracted honey from supers by beekeepers and acquired from different commercial establishments used to validate the multiplex PCR, as well as to conduct a preliminary assessment of the distribution of pathogens (A. apis, N. apis, N. ceranae and P. larvae). The standard technique of this study was effective for diagnosing of the four pathogens in honey of A. mellifera: A. apis, N. apis, N. ceranae and P. larvae. Primers used in both PCR reactions (monospecific and multiplex) for DNA amplification of the target pathogens were precise and sensitive, resulting in products of expected sizes. The formation of nonspecific fragments and/or other artificial PCR products was not observed in multiplex PCR reactions. Thus, this method was suitable for simultaneous detection of the selected pathogens of A. mellifera extracted from honey, and probably can be used in other hive products with minor modifications. The selected pathogens were not found in the honey samples analyzed with this multiplex PCR standardized.